If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(6x + 1) + 7(7x + -1) + -4 = 4 + -6 Reorder the terms: -8(1 + 6x) + 7(7x + -1) + -4 = 4 + -6 (1 * -8 + 6x * -8) + 7(7x + -1) + -4 = 4 + -6 (-8 + -48x) + 7(7x + -1) + -4 = 4 + -6 Reorder the terms: -8 + -48x + 7(-1 + 7x) + -4 = 4 + -6 -8 + -48x + (-1 * 7 + 7x * 7) + -4 = 4 + -6 -8 + -48x + (-7 + 49x) + -4 = 4 + -6 Reorder the terms: -8 + -7 + -4 + -48x + 49x = 4 + -6 Combine like terms: -8 + -7 = -15 -15 + -4 + -48x + 49x = 4 + -6 Combine like terms: -15 + -4 = -19 -19 + -48x + 49x = 4 + -6 Combine like terms: -48x + 49x = 1x -19 + 1x = 4 + -6 Combine like terms: 4 + -6 = -2 -19 + 1x = -2 Solving -19 + 1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 1x = -2 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = -2 + 19 1x = -2 + 19 Combine like terms: -2 + 19 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 3x+46=x+2x-3 | | 5b^2+21b-20=0 | | -1/4f+20.5=12.9 | | 6x-3(3x-4)=30 | | -16+13=m-5 | | 3z+46=1+8z | | 1+1/5p=-7 | | 7x+4(-2x-5)=-31 | | -30n=-27n-57 | | -30n=-27n-57 | | 7b^2-32b-60=0 | | 6x+7-5x=13 | | 2-6p=8 | | 18.9125-(1/4) | | f(0)=-7x^2+9x+7 | | (3x-1)/4=(5x+3)/6 | | 5x+3(-7x-4)=116 | | 5i/3-9i | | 1/5(2x-4)=7 | | 15x-10(1/15+10/15x)=1 | | 4x-12=2x+30 | | -4y(8x)= | | 3g+5=7g+3 | | 6x-5=7x+6 | | 7a=33-4a | | (x+5)/3=(3x-6)/2 | | 1/3x-2/5=0 | | 1/4(7y-1)+1/8(2y+7) | | 6x^2-2xy+7y^2-2=0 | | (2x+1)/3=(4x-7)/5 | | 8x=3x-55 | | 7x+7(-2x-6)=-112 |